Another Chapter in The War On “Woke”: Banning Ethnic Studies and The Anti-CRT Movement by The Unseasoned Elites - Borom, Charles (My University, 2023)
This paper uses critical historicization to trace Arizona educational policy created to ban/halt/undermine ethnic studies efforts.  I illustrate a pattern of suppressing the knowledge of marginalized groups that threatens the established power base built into the social hierarchy meant to perpetuate the status quo. The US education system is one of the most powerful tools in the arsenal of white elites to perpetuate and maintain white supremacy. I use Arizona as a case study to demonstrate how education policy can be weaponized to perpetuate inequities in the US education system. Then, I offer educational policy implications related to the modern iterations of “CRT” bans and these implications demonstrate past-present connections.  My historicization allows for the use of storytelling as a tool to examine the policy environments and  ethnic studies movements. I conclude the paper and illustrate the power of grassroots movements to insulate policy actors from oppressive systems.
University of Minnesota M.A. thesis. May 2023. Major: Organizational Leadership, Policy, and Development. Advisors: Peter Demerath, Nathaniel Stewart. 1 computer file (PDF); ii, 85 pages.